Pengembangan e-Modul Statistika Inovatif Berbasis Multi Representasi - Santia, Ika; Handayani, Aprillia Dwi; Hima, Lina Rihatul; Nurfahrudianto, Aan (Jurnal Math Educator Nusantara: Wahana Publikasi Karya Tulis Ilmiah di Bidang Pendidikan Matematika, 2022)
Mathematical thinking in problem-solving is an important goal of learning mathematics. The ability to use various ways of presenting mathematical concepts (multi-representation) is an important aspect of mathematical thinking. In its implementation, students experience problem-solving failures because of difficulties in making changes from one representation to another. This fact can be seen from the initial observations in statistics class, which showed that out of 37 students, only 12 students were successful in solving statistical problems because they could change verbal and graphic representations to symbolic ones correctly. Meanwhile, 17 out of 25 students failed because they did not understand the problems displayed in graphic form. To overcome this problem, statistical module development research has been carried out by applying the SPSS practice video barcode innovation. The development method uses a modified 4-D model, namely define, design, and develop. Modifications are carried out by eliminating the dissemination stage due to limited time and research costs. Data collection techniques in this study used a questionnaire. The data obtained are qualitative and quantitative. The results showed that the module developed was included in the very feasible criteria, in terms of content feasibility at 85.78%, language feasibility at 88.61%, presentation feasibility at 84.82%, and graphic feasibility at 84.72%. The results of the trial were limited to 37 students who received a positive response of 85,63% so the statistics module was suitable for use as teaching materials.